ترقية الخدمة العمومية بالمرفق العام في ظل الإلإدارة الالالكترونية - عصرنة الجماعات المحلية نموذجا - .رمون, شهرازد (University of Eloued جامعة الوادي, 2017)
لقد شكل موضوع ترقية الخدمة العمومية بالمرافق العامة إنشغالا بارزا لدى السلطات العمومية في الجزائر، ولمواكبة للتطورات المتتالية في استخدام التكنولوجيات الحديثة سعت السلطات إلى عصرنة المرافق الإدارية بإدخال الإدارة الالكترونية كبديل عن الإدارة التقليدية قصد الوصول إلى سرعة ونجاعة في تقديم الخدمات . لذلك جاءت هذه الدراسة للوقوف على بوادر ترقية وتحسين الخدمة العمومية التي كفلها المشرع الجزائري بالعديد من النصوص القانونية استحدثت على مستوى المرافق العامة ، وذلك من خلال تجربة الجزائر في الإدارة الالكتروني ة بالجماعات المحلية والتي تمثل نقطة تحول هامة في واقع الخدمة العمومية ، والتي يتجلى أهم مظاهرها في إستحداث هيئة المرصد الوطني للمرفق العام لمرافقة ترقية الخدمة العمومية ، وتخفيف الإجراءات الإدارية على المواطن ، ومن جهة أخرى تقريب الإدارة من المواطن والحلول محله أمام الجهات القضائية فيما يخص التصحيحات القضائية ، بالإضافة إلى التأثير الذي لعبته الإدارة الالكترونية على تحسين واقع الخدمة العمومية من خلال آليتها المتطورة التي تحقق سرعة الإستجابة في الخدمات المقدمة للمواطنين ورفع مستواها الذي يتطلب تكاثف جميع الأ طراف وضرورة تمتين العلاقة بين الإدارة والمواطن من خلال الحرص على تطبيق النصوص التشريعية الخاصة بهذا المجال وكذا إزالة المعوقات التي تحول دون تطبيق إستراتيجية الإدارة الالكترونية .The subject of devlopping public services by the use of utilities has been a major concern of public anthorities in algeria, which sought to develop administrative utilities through the use of electronic management that depends on new technologies as a substitute for the traditional one , for sake leering up the successive development that read to the speed and efficiency of services delivery . Therefore , this study stands on the of promoting and improving the service public that been guaranteed by the Algerian legislator in law articles. After that , they were developed in the standards of public utilities . Moreover, the Algerian experience in electronic management that is applied in communities should clearly justify these signs of promotion and improvements because it represents an important turning point its most significant manifestations which are developping the national observatory body of public utility to accompany the public service promotion in one side , and to met gate administrative procedures for the citizens , and to approximate the distance between them and administration and also to substitute them before the judicial authorities as regards the legal redresses . As result, the reflection of the use of men developed mechanisms in electronic management had a major effect in improving the reality of public services which are provided to the citizens , as weel as upgrading its level which needs to be all unified to build a powerful relationship by and between the citizens and the administration , and through the application of legislative laws and the removal of obstacles that stands against the application of the strategy of electronic management . Les autorités publics algériennes ont donné une grande importance au sujet la promotion et du développement des services publics en Algérie , elles ont veillé sur la modernisation des secteurs administratifs par l’adaptation de l’administration électronique comme une alternative de l’administration traditionnelle afin d’être à jour avec les nouvelles technologies. C est ainsi que cette étude met l accent le degré de promotion et d amélioration di service public qui été adopte par le législateur algérien avec plusieurs décrets au niveau des secteurs publics , an basant sur l’expérience de l’Algérie en administration électronique avec les collectives locales et qui a été considérée comme une étape très importante dans la réalité du service public , cette étape a mis au monde l’observatoire national du secteur public pour l’accompagnement du service public , elle a aussi fait un allégement de procédures administratives pour citoyen algérien , l’administration dans les corrections juridiques. en outre , l’administration électronique a assure la rapidité des services pour les citoyens par l’ application des décrets donnes par le législateur.
مدكرة ماستر
Keywords: الخدمة العمومية ، الإدارة الالكترونية ، المرفق العام ، الجماعات المحلية; les collectives locales , l’administration électronique , service public; elctronic management , public service, locality communities